(The extent of legal protection against domestic violence in Iraq and Arab countries (Legal Study - Jaber, Nadia ka'ab (Journal of Economic, Administrative and Legal Sciences, 2019)
Family violence is the actual use of force or threat to harm, harm people, and damage property. It is an act that exaggerates aggressive or hostile behavior that results in disturbing or destructive effects that cause psychological or physical harm to people. Others threaten or injure them or attempt to inflict such harm.The Islamic thinkers have dealt with the issue of domestic violence since the beginning of the cradle of Islam, as it was mentioned in one of the hadiths: "Allah is a companion who loves kindness and gives mercy to those who give to violence." The Prophet (peace and blessings of Allaah be upon him) Nor curse) and also saying (peace be upon him) (from the horrors of the Muslim magnificence of God on the Day of Resurrection) and forbade the Prophet to refer the Muslim Muslim brother of the ugliest qualities.Family violence is linked to social ties in the center in which there are, however, its manifestations and forms have evolved and varied in many ways, including: 1. Violence against women2. Domestic violence against children 3. Domestic violence against the elderly.Violence, as defined by laws and constitutions at the founding of the modern state, has taken its official form since the beginning of the 19th century. It has been defined as a phenomenon designed to disrupt the structure of an existing society, thus threatening the system of rights and duties.Therefore, we will address this issue in three sections I on the concept of domestic violence and the second on the causes and types of domestic violence and the third on the laws of protection against domestic violence in the Arab countries.
Keywords: domestic violence; actual use of force; harm; damage